Pengaruh Kesadaran Wajib Pajak, Pengetahuan Perpajakan Dan Kualitas Pelayanan, Terhadap Kepatuhan Wajib Pajak Hotel (Studi Kasus Di Kabupaten Sikka, NTT): (Studi Kasus Di Kabupaten Sikka) - Jaeng, Theresa Yuliana; Yadnyana, I Ketut (Politeknik Ganesha Medan, 2024)
Tax compliance is identical to the recognition of taxpayers in fulfilling their obligations in accordance with tax regulations. Hotel tax arrears are caused by low awareness of hotel taxpayers. Revenue from the hotel business has quite high potential, judging from the number of hotels and inns located in Sikka Regency. The large number of hotel tax arrears that have not been paid by taxpayers results in large hotel tax arrears at the Sikka Regency Regional Revenue Office. This study aims to analyze the effect of taxpayer awareness, tax knowledge, and service quality on hotel taxpayer compliance. Data from explanatory research with a quantitative approach. The number of samples used was 42 samples with saturated sampling method. The number of respondents in this study were 84 respondents. Data collection was done by distributing questionnaires. The data analysis technique used is path analysis using Partial Least Square 3.2.8 software. The results showed that taxpayer awareness, tax knowledge, and service quality had a positive effect on hotel taxpayer compliance. The more taxpayers are aware of their obligations have a good understanding of taxes, the higher the taxpayer compliance. In addition, the better the facilities and services provided by the tax authorities, the higher the level of taxpayer compliance. Local governments, especially the Sikka Regency Regional Revenue Agency (Bapenda), can play an active role in providing socialization about taxation that can increase the understanding of taxpayers of tax regulations so as to help increase taxpayer compliance and local tax revenue of Sikka Regency.